2022
DOI: 10.3389/fpsyg.2021.610874
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Alliance in Cognitive Behavioural Therapy in Child and Adolescent Mental Health-Current Trends and Future Challenges

Abstract: This extended literature review proposes to present the trends in the therapeutic alliance, outcomes, and measures in the last decade within the premises of individual cognitive behaviour therapy (CBT) and its innovations, used as an interventional measure in the context of child and adolescent mental health setting. A brief background of the rationale for conducting this literature search is presented at the start. This is followed by the methodology and design which incorporates the inclusion and exclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…This alliance is fundamental to the success of any face-to-face psychological therapy. Previous studies have also highlighted this challenge [35,39] and have suggested that it is possible to develop this alliance [40,41], although it may have unique and yet unconfirmed characteristics [42], particularly when working with children [43]. The finding that young people, despite being comfortable using technology, did not prefer videoconferencing is perhaps due to their desire to maintain confidentiality.…”
Section: Discussionmentioning
confidence: 99%
“…This alliance is fundamental to the success of any face-to-face psychological therapy. Previous studies have also highlighted this challenge [35,39] and have suggested that it is possible to develop this alliance [40,41], although it may have unique and yet unconfirmed characteristics [42], particularly when working with children [43]. The finding that young people, despite being comfortable using technology, did not prefer videoconferencing is perhaps due to their desire to maintain confidentiality.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis with over 35,000 adults found that users reported forming a therapeutic alliance with Woebot [20]. Therapeutic alliance, a construct familiar in psychotherapeutic treatment outcomes research, refers to the therapeutic relationship and affective bond between provider and patient and is associated with the efficacy of psychotherapy [26,27]. A randomized controlled pilot among adolescents aged 13-17 years (n=17) demonstrated W-GenZD's preliminary feasibility and utility in an outpatient primary care pediatric setting [28], but further evaluation of its feasibility and acceptability as well as clinical efficacy is warranted.…”
Section: Technology-leveraged Mh Care Interventionsmentioning
confidence: 99%